2022
DOI: 10.1093/braincomms/fcac175
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex pedigree with pathologically confirmed multiple system atrophy and Parkinson’s disease with dementia

Abstract: Multiple system atrophy is considered a sporadic disease, but neuropathologically confirmed cases with a family history of parkinsonism have been occasionally described. Here we report a North-Bavarian (colloquially, Lion’s tail region) six-generation pedigree, including neuropathologically confirmed multiple system atrophy and Parkinson’s disease with dementia. Between 2012 and 2020, we examined all living and consenting family members of age and calculated the risk of prodromal Parkinson’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The molecular basis of MSA remains unknown; it is primarily considered a sporadic disease with no clear environmental or genetic risk factors identified. However, notable exceptions exist, particularly in certain familial cases with confirmed MSA pathology and autosomal dominant or recessive inheritance pattern observed in European and Asian pedigrees [4]. One puzzling genetic finding in MSA involves functionally impaired variants of the COQ2 gene.…”
Section: Geneticsmentioning
confidence: 99%
“…The molecular basis of MSA remains unknown; it is primarily considered a sporadic disease with no clear environmental or genetic risk factors identified. However, notable exceptions exist, particularly in certain familial cases with confirmed MSA pathology and autosomal dominant or recessive inheritance pattern observed in European and Asian pedigrees [4]. One puzzling genetic finding in MSA involves functionally impaired variants of the COQ2 gene.…”
Section: Geneticsmentioning
confidence: 99%
“…1 A family history (FH) for parkinsonism or other neurodegenerative disorders may in fact occur in people with MSA, but the contribution of genetic factors to MSA pathogenesis is not fully understood to date. 3,4 Here we retrospectively assessed the frequency rates of FH for parkinsonism, dementia, tremor, ataxia, or motor neuron disease within first-to-third-degree relatives of people included in the Innsbruck MSA Registry (n = 144), and compared them with historical MSA cohorts (cumulative n = 1173), Innsbruck-based PD cases (n = 226), and published population-based controls (cumulative n = 20,784). A detailed methodological description is provided in Supplementary Document 1.…”
Section: Family History For Neurodegeneration In Multiplementioning
confidence: 99%
“…Pathogenic loss-of-function and missense mutations in SORL1 have been postulated to affect APP shuttling between the trans-Golgi network and early endosomes, leading to disease. 4 Interestingly, several studies have also found rare SORL1 mutations in patients with Alzheimer's disease with concomitant LBD, suggesting that SORL1 may be a pleiotropic risk gene. [4][5][6] Here, we assessed the possible association of SORL1 variants with risk for LBD.…”
Section: Evaluation Of Sorl1 In Lewy Body Dementia Identifies No Sign...mentioning
confidence: 99%
See 2 more Smart Citations